Impact of FLD on vegetable pigeonpea (Cajanus cajan) variety 'Vaishali' under rainfed condition of central Gujarat (Indian Journal of Arid Horticulture, 2020)
Traditionally, pigeonpea [Cajanus cajan (L.) Millsp.] cultivated for grain seed but for vegetable purpose, pods are harvested when it is immature. In Gujarat, it is used as substitute of green pea [Pisum sativum (L.)]. Pigeonpea is as one of the most important pulse crops of the Panchmahals district of Gujarat. However, productivity of pigeonpea in this district is very low. Attempts were made to improve productivity and to increase area under pigeonpea by adopting high yielding variety (Vaishali). In order to compare conventional pigeonpea with HYVs, 75 front line demonstrations were carried out in systematic manner on farmers' field to show the worth of a new varieties in comparison to local check and thereby convincing farmers about potentialities of improved variety and advance production management practices for adoption. The yield (green pod) in HYVs was recorded 80q/ha whereas it was 45q/ha in local check. Similarly, the benefit cost ratio for HYVs was estimated to 3.9 as compared to local check (2.5). The impact of FLDs was standardized which showed improvement in knowledge of pigeonpea cultivation and higher level of satisfaction in terms of its culinary uses and economic gain resulted into mass scale adoption of HYVs in Panchmahal district (Gujarat).
Keywords: Frontline demonstration; pigeonpea; production technology